Colorectal cancer with liver metastases: Neoadjuvant chemotherapy, surgical resection first or palliation alone? - Khan, Khurum (Baishideng Publishing Group Inc, 2014)
Colorectal cancer (CRC) is one of the commonest cancers with 1.2 million new cases diagnosed each year in the world. It remains the fourth most common cause of cancer-related mortality in the world and accounts for > 600000 cancer-related deaths each year. There have been significant advances in treatment of metastatic CRC in last decade or so, due to availability of new active targeted agents and more aggressive approach towards the management of CRC, particularly with liver-only-metastases; however, these drugs work best when combined with conventional chemotherapy agents. Despite these advances, there is a lack of biomarkers to inform us about the accurate management of the patients with metastatic CRC. It is therefore imperative to carefully select the patients with comprehensive multi-disciplinary team input in order to optimise the management of these patients. In this review we will discuss various treatment options available in management of colorectal liver metastases with potential guidance on how and when to choose these options along with consideration on future directions in management of this disease.